2021
DOI: 10.46747/cfp.6705357
|View full text |Cite
|
Sign up to set email alerts
|

Assessing undergraduate medical education through a generalist lens

Abstract: Problem being addressed Medical schools aim to integrate the values of generalism into their undergraduate programs. However, currently no program has been described to measure the degree to which formal curricular materials represent generalist principles. Objective of programTo quantify the generalism principles present in undergraduate medical education learning materials and to provide recommendations to enhance generalism content.Program description A review of the literature and accreditation documents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…This approach has recently gained momentum in undergraduate and post-graduate medical education. 11 Our findings support the importance of the generalist and the tenets of generalism, particularly the portrayal of the whole person and contextual factors, and respect for the role and scope of practice of generalists. 11 The clinical heuristics of GPs may provide medical students a less reductionist and siloed approach to CAMH learning.…”
Section: Impact Of No Facilitatorsupporting
confidence: 73%
See 1 more Smart Citation
“…This approach has recently gained momentum in undergraduate and post-graduate medical education. 11 Our findings support the importance of the generalist and the tenets of generalism, particularly the portrayal of the whole person and contextual factors, and respect for the role and scope of practice of generalists. 11 The clinical heuristics of GPs may provide medical students a less reductionist and siloed approach to CAMH learning.…”
Section: Impact Of No Facilitatorsupporting
confidence: 73%
“…11 Our findings support the importance of the generalist and the tenets of generalism, particularly the portrayal of the whole person and contextual factors, and respect for the role and scope of practice of generalists. 11 The clinical heuristics of GPs may provide medical students a less reductionist and siloed approach to CAMH learning. Furthermore, inclusion of the generalist in teaching regarding a subspecialty is a model for collaboration and interdisciplinary respect in future clinical care.…”
Section: Impact Of No Facilitatorsupporting
confidence: 73%
“…4 The idea was to emphasise relevancy in primary care and to highlight what is frequent, and what is not. 5 On the other hand, the analysis showed that there is a wide spectrum of rarer skin-related conditions encountered in primary care. These were incorporated in perceptive learning modules and internet-based learning tools.…”
Section: Dermatology Teacher Have You Critically Evaluated the Conten...mentioning
confidence: 99%
“…These were now shifted to represent the most important material of the curriculum and trained intensively with bedside teaching, problem‐orientated learning and small group teaching 4 . The idea was to emphasise relevancy in primary care and to highlight what is frequent, and what is not 5 . On the other hand, the analysis showed that there is a wide spectrum of rarer skin‐related conditions encountered in primary care.…”
mentioning
confidence: 99%
“…7 This work is complemented by a valuable article by Dr Melissa Nutik et al entitled "Assessing undergraduate medical education through a generalist lens," which describes a tool they developed and evaluated to assess the generalist content of undergraduate medical curricula (page 357). 8 Finally, editorial fellow Dr Sarah Fraser shines a light on one of the darker aspects of being a generalist (page 367). 9 Every generation of family physicians and GPs faces challenges-medical, cultural, and societal-that force us to reevaluate what it means to be a generalist.…”
mentioning
confidence: 99%